Pengelolaan SDM UMKM Kuliner Binaan di Cempaka Putih Jakarta Pusat - Lies Putriana; Chaerani Nisa; Dian Riskarini (SULUH: Jurnal Abdimas, 2020)
MSMEs has also contributed to the national economy. However, this sector is unable to develop optimally due to variety of fundamental weaknesses. One of the weaknesses is in regards to Human Resource management and the inability to properly implement its functions which has affected the performance of MSME. Community Service Program was conducted by FEB-UP in collaboration with PT. Sinar Sosro in order to find solutions towards the challenges faced by the culinary SMEs in Cempaka Putih Through interviews, discussions and giving direct understanding of good human resource management, we hoped that the MSME actors will be able to understand to make of plans for development, improvement and evaluation of the performance of these culinary MSME actors. From the results of visits, discussions and direct interviews to the field, it was found that the performance of MSME actors was not optimal, such as the simple division of tasks, the administration of sales that was not neat and the provision of compensation that had not been measured. It is hoped that the results of these activities will provide benefits for the improvement of HR management which will have an impact on increasing the business results of these culinary MSMEs.